Pembuatan Kalsium Glukonat Dari Batu Kapur Bukit Tui Padang Panjang - Zulharmita Zulharmita; Sri Indah Kesuma; Fithriani Armin (Jurnal Farmasi Higea, 2014)
A study concerning the manufacture of calcium gluconate limestone hill Tui Leopold. Previous limestone samples were identified and determined the levels of calcium. 1 g sample of limestone calcium levels obtained 36,0812 %. In the manufacture of calcium gluconate used limestone samples of 20 g were dissolved in 6 M HCl, filtered and the filtrate was added 6 M NH4OH to pH 10 . Then added gluconic acid 1 M. The precipitate is filtered, washed, dried in an oven at a temperature of 1050 C. The results obtained as 6,2084 g of calcium gluconate. Examination of limestone calcium gluconate include organoleptic examination, solubility, qualitative identification, examination and the melting point of the assay by the method complexometry. In the assay of calcium gluconate from the manufacture of natural limestone samples carefully weighed approximately 0,5 g , 1 g, and 2 g. Of the three differences in weight percentage of calcium gluconate calcium results obtained, weighing 0,5 g to as much as 62,2708 % , 1 g weight as much as 79,9048 %, while the weight of as much as 2 g 101,7232 %. From the results of the assay of calcium gluconate with a sample of 6,2084 g drying results have percentage 101,7232 % with the results of testing the melting point is 2000 C calcium gluconate. It can be concluded natural limestone hill Tui Leopold has a high purity calcium levels that can be made of calcium gluconate.